Therapeutic Approaches to Dysautonomia in Childhood, with a Special Focus on Long COVID - Reiner Buchhorn (MDPI AG, 2023)
Background: Dysautonomia seems to be important for the pathophysiology of psychosomatic diseases and, more recently, for long COVID. This concept may explain the clinical symptoms and could help open new therapeutic approaches. Methods: We compared our data from an analysis of heart rate variability (HRV) in an active standing test in 28 adolescents who had developed an inappropriate sinus tachycardia (IST, n = 13) or postural orthostatic tachycardia syndrome (POTS, n = 15) after contracting COVID-19 disease and/or vaccination with 64 adolescents from our database who developed dysautonomia due to psychosomatic diseases prior to the COVID-19 pandemic. We prove the effects of our treatment: omega-3 fatty acid supplementation (O3-FA, n = 18) in addition to propranolol (low dose, up to 20-20-0 mg, n = 32) or ivabradine 5-5-0 mg (n = 17) on heart rate regulation and heart rate variability (HRV). Results: The HRV data were not different between the adolescents with SARS-CoV-2-related disorders and the adolescents with dysautonomia prior to the pandemic. The heart rate increases in children with POTS while standing were significantly lower after low-dose propranolol (27.2 ± 17.4 bpm***), ivabradine (23.6 ± 8.12 bpm*), and O-3-FA (25.6 ± 8.4 bpm*). The heart rate in children with IST while lying/standing was significantly lower after propranolol (81.6 ± 10.1 bpm**/101.8 ± 18.8***), ivabradine (84.2 ± 8.4 bpm***/105.4 ± 14.6**), and O-3-FA (88.6 ± 7.9 bpm*/112.1/14.9*). Conclusions: The HRV data of adolescents with dysautonomia after COVID-19 disease/vaccination are not significantly different from a historical control of adolescents with dysautonomia due to psychosomatic diseases prior to the pandemic. Low-dose propranolol > ivabradine > omega-3 fatty acids significantly decrease elevated heart rates in patients with IST and the heart rate increases in patients with POTS and may be beneficial in these children with dysautonomia.